MPC-based control strategy of PV grid connected inverter for damping power oscillations - Wen, Xichang; Wu, Ting; Jiang, Hui; Peng, Jianchun; Wang, Huaizhi (Frontiers in Energy Research, 2022)
With the global warming and the depletion of fossil energy, the development of photovoltaic (PV) energy has been highly valued by many countries. However, when large-scale PV power stations are connected to the power grid through inverters, the inertia and damping capacity of the power system will be greatly reduced, which will cause frequent power oscillations occur in the power system. In order to solve this problem, a control strategy of PV grid-connected inverter based on the model predictive control (MPC) algorithm is proposed in this paper. Based on the MPC algorithm and established discrete time predictive model, the PV grid-connected inverter dynamically adjusts its output current to achieve the effect of suppress the power oscillation. Finally, the simulation results show that the proposed control strategy is effective in damping power oscillation of power grid and enhance power system stability.